Development of android-based gamification for hikayat text learning - Diana, Purwati Zisca; Sulistiyono, Roni; Zultiyanti, Zultiyanti; Iswatining, Daroe (Universitas Ahmad Dahlan, 2024)
Research on the use of learning media has great significance in helping teachers and students overcome learning challenges. The latest innovation in this research is the development of Android-based gamification learning media targeted at high school grade X students in learning Indonesian hikayat text. The research aims to analyze the need for learning media for teachers and students, and develop the media. The research method used is research and development with a modified approach from Borg & Gall adapted by Sugiyono. Data were collected through interviews, questionnaires, observation, and documentation, with product validation by three experts. The subjects of this research were teachers and students from SMAN 1 Kalasan, Sleman, Yogyakarta. The results of the needs analysis showed the need for learning media that is more interesting, interactive, and in accordance with current technology. Meanwhile, the evaluation results of the Android-based gamification media showed positive responses from teachers and students, with increased student engagement and effectiveness of material delivery by teachers, as well as students' interest in learning and better understanding of hikayat text.